Epic / 1. - Kostick, Conor, 1964- (Epic, 2007)
On New Earth, a world based on a video role-playing game, fourteen-year-old Erik pursuades his friends to aid him in some unusual gambits in order to save Erik's father from exile and safeguard the futures of each of their families.